Cover crop mixtures increase ecosystem multifunctionality in summer crop rotations with low N fertilization - Restovich, Silvina Beatriz (2022)
Cropping diversification with cover crop mixtures combined with low N fertilization represents an ecological alternative that may promote sustainability. Our objective was to evaluate changes on soil organic fractions and structure, cover crop biomass, and main crop yield 5 years after the introduction of two cover crop mixtures, oats+forage radish (CC1) and oats+forage radish+vetch (CC2), in a soybean-soybean and maize-soybean sequence with low N fertilization of maize. After 5 years, the soil from sequences with cover crops had higher concentrations of soil organic carbon (SOC) (23.3 vs 20.1 g kg−1), soil organic nitrogen (SON) (2.4 vs 2.0 g kg−1), and particulate organic carbon (POC) (4.4 vs 2.9 g kg−1) at 0–5 cm depth than the controls without cover crops, in association with C input from cover crops aboveground biomass, which averaged 2.2 and 3.0 Mg ha−1 year−1 for CC1 and CC2, respectively. Soil aggregation at 0–5 cm depth was more stable with than without cover crops (33.4 vs 16.4%), and it was positively related to SOC (R2 = 0.44, p < 0.01) and POC (R2 = 0.50, p < 0.01) concentrations. Soil from CC2 had a higher proportion of macropores and mesopores over 300 μm than soil from CC1 and the controls without cover crops at 0–5 and 10–30 cm depth, respectively. Maize yield was affected by rainfall: it was similar among treatments in dry growing seasons (<5.0 Mg ha−1) and higher in CC2 and the control without cover crops than in CC1 in more humid seasons (9.2 vs 7.9 Mg ha−1). Soybean yield was similar among treatments except after dry cover crop growing seasons, when control treatments yielded more than cover crop treatments (3.4 vs 2.8 Mg ha−1). This study demonstrates that summer crop sequences with cover crop mixtures increase ecosystem multifunctionality and that including vetch in the mixture increases its production potential and benefits, especially in the soybean-soybean sequence.